Let us consider the method from this book (http://scipp.ucsc.edu/~haber/ph116C/Wronskian_12.pdf page 4)
Let the general solution be
"y(t) =c_1y_1(t) +c_2y_2(t) +y_p(t)," "y_1, y_2" are the solutions of the homogeneous equation. These solutions may be obtained by the characteristic equation "\\lambda^2 -3\\lambda + 2 = 0 , \\;\\;\\; \\lambda_1 = 1, \\lambda_2 = 2 \\; \\Rightarrow \\; y_1 = e^t, \\; y_2 = e^{2t}" .
Let us calculate the Wronskian:
"W = \\det \\begin{pmatrix}\n y_1 & y_2 \\\\\n y_1' & y_2'\n\\end{pmatrix} = y_1y_2'-y_2y_1' = e^t\\cdot2e^{2t} - e^{2t}\\cdot e^t = e^{3t}."
"y_p(t) = -y_1(t)\\int\\dfrac{y_2(t)}{W(t)}f(t)\\,dt + y_2(t)\\int\\dfrac{y_1(t)}{W(t)}f(t)\\,dt = \\\\\n= -e^t\\int\\dfrac{e^{2t}}{e^{3t}}\\cdot\\dfrac{e^{2t}}{e^t+1}\\,dt + e^{2t}\\int\\dfrac{e^{t}}{e^{3t}}\\cdot\\dfrac{e^{2t}}{e^t+1}\\,dt = -e^t\\int \\dfrac{e^t}{e^t+1}\\,dt + e^{2t}\\int \\dfrac{1}{e^t+1}\\,dt = -e^t\\ln(e^t+1) + e^{2t}(t-\\ln(e^t+1)) = te^{2t} - \\ln(e^t+1)\\cdot(e^t+e^{2t})."
Therefore, the solution is
"y(t) =c_1y_1(t) +c_2y_2(t) +y_p(t) = c_1e^t+c_2e^{2t} + te^{2t} - \\ln(e^t+1)\\cdot(e^t+e^{2t})."
Comments
Leave a comment